Consumption of wild edible plants in the Kofale and Heban-Arsi districts, West Arsi Zone, Oromia Regional State, Ethiopia - Geritu Nuro; Ketema Tolossa; Mirutse Giday (Journal of Ethnobiology and Ethnomedicine)
Abstract Background Wild edible plants (WEPs) are neglected and have received little attention despite their significant contributions to the sustenance and livelihoods of rural communities. This study was conducted in the Kofale and Heban-Arsi districts of the Oromia Regional State, Ethiopia, to document the diversity, to assess the most preferred WEPs, their utilization, and threats they face. Methods The study was conducted in the Kofale and Heban-Arsi districts of the West Arsi Zone of the Oromia Regional State, Ethiopia. Data collection took place from February to September 2022 in Kofale and from November 2022 to April 2023 in Heban-Arsi district. To gather ethnobotanical information, the research employed semi-structured interviews, field observations, focus group discussions, and guided field walks. The interviews involved 290 informants who were selected via snowball sampling and systemic random sampling methods. Preference ranking values, direct matrix rankings, and use values (UVs) of documented species were computed. Results A total of 62 WEPs species belonging to 38 families and 56 genera were identified. The Moraceae family includes 7 species, followed by Fabaceae and Rubiaceae (each 4 species), and Lamiaceae (3 species). Shrub was the dominant growth form (32 species), followed by herbs (13 species). The largest number (24 species) of WEPs was collected from grazing lands/fields, followed by forest habitats (17 species). The most widely used edible plant part was fruit (40 species) and leaf (11 species). Most WEPs were collected for consumption from March to May (30 species), and the majority of the species (48, 77.4%) were utilized in their raw state. A large number of WEP (41 species) were consumed only during periods of food shortage, and the remaining (21 species) were used as staple food supplements. Multiple other uses of WEPs in the study area also reported. Fifty-two species mentioned for medicinal use, and the species that had the highest use value was Cordia africana Lam. (0.9). The direct matrix ranking results indicated that agricultural expansion was a principal threat to the WEPs in the study area. Conclusion This study indicated that WEPs are widely used during food shortages in the study area, but many WEP species are under threat due to growing pressure from various anthropogenic factors. Thus, public awareness and community-based management need to be encouraged at all levels to conserve and sustainably use these resources to address food insecurity.